2019
DOI: 10.1007/s10209-019-00686-7
|View full text |Cite
|
Sign up to set email alerts
|

Teachers as designers of formative e-rubrics: a case study on the introduction and validation of go/no-go criteria

Abstract: Information and Communications Technologies (ICTs) offer new roles to teachers to improve learning processes. In this regard, learning rubrics are commonplace. However, the design of these rubrics has focused mainly on scoring (summative rubrics), whereas formative rubrics have received significantly less attention. ICTs make possible electronic rubrics (e-rubrics) that enable dynamic and interactive functionalities that facilitate the adaptable and adaptive delivery of content. In this paper, we present a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Some studies have shown the positive impact of assessment e-rubrics. Studies reported that e-rubrics are effective tools for performing formative and summative assessments [14,18,1,15], promoting self-assessment [21], and measuring soft skills in Art subjects-both related to peer and self-evaluation [12]. E-rubrics are powerful resources for peer assessment [17].…”
Section: E-rubrics For Assessmentmentioning
confidence: 99%
“…Some studies have shown the positive impact of assessment e-rubrics. Studies reported that e-rubrics are effective tools for performing formative and summative assessments [14,18,1,15], promoting self-assessment [21], and measuring soft skills in Art subjects-both related to peer and self-evaluation [12]. E-rubrics are powerful resources for peer assessment [17].…”
Section: E-rubrics For Assessmentmentioning
confidence: 99%
“…Thus, the formative assessment supports an iterative process of learner‐regulated development (Panadero et al, 2013; Van Aalst et al, 2011). Rubrics are being implemented as a tool to support learner regulated development, as they provide a detailed account of the interrelated parts or ‘sub‐skills’ that make up a complex skill, such as presentation, collaboration, and information literacy (Panadero et al, 2012) and provides the learner with feed‐up, feedback, and feedforward (Company et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A typical approach to rectify this issue is to disaggregate the complex criteria into a series of more understandable criteria of lower conceptual difficulty. A problem arises when a compact list of abstract or dense criteria is replaced by a long list of simpler ones, which in many cases can make them impractical and time-consuming" [32]. Johansson et al [33] recommend using model qualities with the help of the scoring system detailed in [32].…”
Section: Introductionmentioning
confidence: 99%
“…A problem arises when a compact list of abstract or dense criteria is replaced by a long list of simpler ones, which in many cases can make them impractical and time-consuming" [32]. Johansson et al [33] recommend using model qualities with the help of the scoring system detailed in [32]. Here too, however, the research only pertains to the checking and evaluation of the CAD model structure.…”
Section: Introductionmentioning
confidence: 99%